Out in Central Pennsylvania : The History of an LGBTQ Community - Burton, William, 1950-; Loveland, Barry (Book collections on Project MUSE., 2020)
"Examines the rise and development of an LGBTQ community in the heart of Central Pennsylvania, and how gay identity and social and advocacy networks form outside of a large urban environment"--